Peace Education, Transformation, and Responding to Climate Chaos (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
Peace education rooted in an analysis of structural, cultural, and direct violence provides a vehicle for an anti-capitalist, pro-indigenous, and spiritually-grounded methodology to examine climate chaos. Through autoethnographic reflection, the author reviews the root causes that led us to planetary disaster, analyzes peace education responses, and shares peace-education-based climate education models to transform our teaching and our relationship to Earth.
Keywords: climate change; climate chaos; transformation; root causes of climate change; Earth Centered